Reliability and Validity of a Chinese Version of the STEM Attitude Scale for Primary and Secondary School Students - Yanjun Zhang (MDPI AG, 2021)
In recent years, STEM (science, technology, engineering, mathematics) education has received widespread attention from all over the world, and there are not many studies on STEM attitudes in China. One of the reasons is the lack of measurement tools that have been tested for reliability and validity. The Chinese version STEM attitudes scale for primary and secondary schools is a multidimensional scale that measures the STEM attitudes of primary and secondary school students. It consists of three subscales: STEM interest, 21st-century skills confidence, and STEM career interest. In order to test the reliability and validity of the scale application, as well as understand and improve the STEM attitudes of primary and secondary school students, the research team surveyed and collected 566 responses from primary and secondary school students in Zhejiang, Shanghai, Shandong, Liaoning, and other places. After exploratory factor analysis, confirmatory factor analysis, and a reliability and validity test, the scale finally retained 48 items. The scale supports a hypothetical five-factor model with good reliability and validity and can be used to assess STEM attitudes in Chinese primary and secondary schools. This research also shows that students’ STEM interests and STEM career interests showed clear variation among different genders, grades, and parental education levels.